Analysis Of The Relationship Between Financial Technology (Fintech) And Financial Planning And Control Of Millennial Households - Beni Sucipto; Nurianah; Ninis Umnastuti (Institut Teknologi dan Bisnis Yadika, 2026)
This study aims to analyze the relationship between the use of Financial Technology (FinTech) and household financial planning and control among millennials running micro, small, and medium enterprises (MSMEs) in the furniture sector in Mojowarno District, Jombang Regency. The development of FinTech provides various conveniences in financial management, but there are still gaps in its utilization, especially among MSMEs. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 50 millennial respondents who are MSME furniture operators, and analyzed using the Pearson correlation test and multiple linear regression. This study used SPSS Version 24 analysis tools. The results show a positive and significant relationship between FinTech use and household financial planning, as well as more effective financial control. These findings indicate that the use of FinTech plays an important role in supporting the financial stability of millennial households while increasing the efficiency of business financial management. This research is expected to become a basis for the development of digital financial education for MSMEs, especially in the furniture sector.